Analisis Penerapan Akuntansi Biaya Lingkungan Pada PT Ratna Jaya Pekalongan - Tjioe Denise Sheila Pramana; M. Devita Putri Nilamsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Environmental costs play an important role in reducing environmental problems and maintaining business sustainability. This research takes the research object at PT. Ratna Jaya is a private company operating in the batik convection sector. The company's production These activities have the potential to negatively impact on the environment. The purpose of this investigation is to determine and analyze the application of environmental costs in PT Ratna Jaya Pekalongan. This investigation is a qualitative descriptive investigation with a case study model. Sources and types of data to be used include primary and secondary data. The data analysis technique for the investigation using the case study method is the supporting coincidental data analysis technique. The results of the investigation show that there are five steps in the allocation of environmental costs. The identification stage shows that there are two groups of environmental costs identified, namely operational costs (including chemical costs, spare parts maintenance costs, workshop costs, PLN electricity costs, electricity maintenance costs and labor wages) and legal costs. The recognition stage shows that the environmental cost recognition method chosen is the accrual basis method. The measurement stage shows that the environmental cost measurement method chosen is the Historical cost method. The presentation stage shows that environmental costs are presented together in the income statement. The disclosure stage indicates that environmental costs are disclosed in the income statement. Keywords: Environmental Accounting; Environmental Costs; Waste Management